DEVELOPMENT OF HAJJ & UMRAH HEARTBEAT, HEART RATE AND BODY TEMPERATURE USING MIOT - Muhammad Hakimi bin Mohd Nashron; Shah Rizailli bin Mukhtar; Ustaz Haji Abdullaah bin Feisal (Journal of Engineering Technology, 2022)
Hajj is one of the ritual duties of a Muslim, which is one of the most extraordinary experiences in the life of a Muslim. For example, Hajj is an annual pilgrimage to Mecca in Saudi Arabia. The Hajj is a show of the unity and adherence of the Muslim m to Allah Ta’ala. Pilgrims have always been recorded every hour during the Hajj or Umrah. In addition, we also have been shocked by the pandemic Covid-19. This project design is in the shape of a wearable device that will apply to the wrist. Commonly, the pilgrim’s health was diagnosed at a late stage by the medical center at the airport, which already had multi-complication such as high Fever (hyperpyrexia). Other than that, due to the increment of causes related to pilgrims performing Hajj and Umrah such as MersCoV or Covid-19 Virus with different variant types, each of the Covid-19 variants has its side effect will include traveler that traveled to infection region. Arduino, Circuito.io, Multi-sim, and Proteus have as the software to design and simulate the circuit. All the data will be display on pilgrim’s and Mutawwif’s smartphones by using Blynk Apps. The regular reading of heart rate/heartbeat for an average person will be 60 bpm to 120 bpm. In an emergency, the pulse rate can help determine if the heart is pumping enough blood. Pulse rate helps to find the cause of symptoms such as an irregular or rapid heartbeat (pulse), fainting, dizziness, chest pain, or shortness of breath. This project will solve the problem that pilgrims commonly face. This wearable device has three main inputs: a heart rate/Heartbeat, Sp02, and an infrared body temperature sensor as precaution data. Other than that, this project will reduce the number of cases that happen to pilgrims. This wearable device can also be a step precaution by using it while performing Hajj and Umrah. This device will help Mutawwif a lot in monitoring pilgrim’s health monitor without any obstacles. As nowadays, the implementation of IoT giving positive changes and convenience to its consumers.